Performance of End Anchored Steel Plate and Cfrp Laminate Flexurally Strengthened R.C. Beams - Jumaat, Mohd Zamin; Alam, M.A. (2009)
Strengthening of reinforced concrete structures is an important task in the field of structural maintenance. Different types of strengthening materials and methods are available in the market for this purpose. These include Ferro cement, sprayed concrete, steel plate and fibre reinforced polymer (FRP) laminate. However, plate bonding methods using steel plates and carbon fibre reinforced polymer (CFRP) laminates are popular and most widely used in this field. The main objective of this research is to investigate the behaviour of steel plate and CFRP laminate flexurally strengthened reinforced concrete beams. A total of five beams, each 2300 mm long, 125 mm wide, and 250 mm deep, were fabricated and tested. One beam was left un-strengthened to act as the control beam. Out of four beams two beams were strengthened with steel plates and another two beams were strengthened with CFRP laminates. From each of the steel plate and CFRP laminate strengthened beams, one beam was anchored using L shape end anchors to avoid premature failure. The anchorage length of end anchors is obtained from the design calculation. The experimental results showed that the strengthened beams had higher failure load, good failure modes, less deflections and better cracking patterns over the control beam. It is also seen that strengthened beams with end anchors showed higher failure loads and more ductile behaviour compared to the un-anchored strengthened beams.